Case report of Lafora disease: a rare genetic disorder manifesting as progressive myoclonic epilepsy - Naderian, Ramtin; Vafaeian, Farzane; Hoseini, Seyyed Mohamad; Sanami, Samira (BMC neurology, 2025)
Background Lafora disease (LD) is a rare, autosomal recessive progressive myoclonic epilepsy caused by mutations in EPM2A or EPM2B. It is characterized by abnormal glycogen metabolism leading to poly-glucosan deposits, known as Lafora bodies, in various tissues. LD typically manifests during adolescence with progressive neurological decline, including myoclonic seizures, cognitive impairment, and ataxia. Early diagnosis is critical for symptom management, yet the disease remains challenging to treat due to its refractory nature. Case presentation We report the case of a 15-year-old male who initially presented with tonic-clonic and myoclonic seizures, bilateral lower limb paralysis, and hand tremors. Despite normal initial imaging findings, subsequent clinical progression raised suspicion for progressive myoclonic epilepsy. Genetic testing identified a homozygous pathogenic variant in EPM2A, confirming the diagnosis of LD. electroencephalogram (EEG) findings evolved over time, showing generalized spikes, poly-spikes, and spike-wave complexes on a slow background, consistent with advanced LD. The patient’s seizures proved refractory to standard anti-epileptic drugs, necessitating the addition of phenobarbital, metformin, and zonisamide, which eventually achieved partial seizure control. Family genetic screening identified heterozygous carriers without clinical symptoms, emphasizing the need for genetic counseling. Conclusions This case highlights the diagnostic challenges of LD, particularly in its early stages when clinical and imaging findings may be nonspecific. The report underscores the importance of genetic testing in confirming the diagnosis and tailoring management strategies. Despite limited treatment options, individualized multi-drug regimens may help achieve partial symptom control. Early recognition and comprehensive management, including family counseling, are essential in improving quality of life for patients and their families.